The e-mobility market in road transport of Poland and Germany - Wodnicka, Monika; Malinowski, Michał (Contemporary challenges of transport, freight forwarding and logistics - selected aspects, 2023)
The aim set by the authors of this study is to present the e-mobility market in the light of statistical data. A reference was made to the essence and determinants of electromobility of road transport. The main regions in the global market recognized as leaders of e-mobility both in sales and in the amount of charging infrastructure for electric cars were indicated. Also, an assessment of Poland's position in the development of e-mobility was undertaken. For this purpose, a comparative analysis was carried out with Germany, one of the European Union countries considered a leader in transport electrification. The analysis made use of pre-existing data from statistical databases, reports, and studies of industry services.